2017
DOI: 10.1016/j.ceramint.2016.11.222
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and ferroelectric/dielectric properties of La-doped PMN-PT ceramics with high optical transmittance

Abstract: Relaxor ferroelectric 0.75(Pb 1-3x/2 La x)(Mg 1/3 Nb 2/3)O 3-0.25(Pb 1-3x/2 La x)TiO 3 (La 3+ :PMN-PT x/75/25, where x = 2.8, 3.0, 3.5, and 4.0 mol% of La 3+) transparent ceramics were fabricated by the combination of oxygen atmosphere pressureless sintering and hot-pressing sintering process. The optical transmittances of above four ceramics are higher than 60% at the wavelength of 500-900 nm. La 3+ :PMN-PT 3.0/75/25 exhibits the highest transparency around 70% at 900 nm which is very close to the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Li et al reported that the extinction coefficient of Mn-doped 0.15Pb(In 1/2 Nb 1/2 )O 3 -0.57Pb(Mg 1/3 Nb 2/3 )O 3 -0.28PbTiO 3 (PIN-PMN-PT) single crystal is 0.0023 at 350 nm and decreases sharply to zero when the wavelength increases to larger than 450 nm. [22] X-ray diffraction (XRD) results in Figure S1a in the Supporting Information indicate that Sm-doped PMN-PT ceramics are all pure perovskite phase with pseudocubic structure, similar with La-doped PMN-PT transparent ceramics reported by Song et al [16] The single pseudocubic phase structure makes the birefringence scattering and secondary phases scattering negligible. Scattering loss caused by residual pores has been confirmed to be the main cause of the attenuation of the light intensity.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Li et al reported that the extinction coefficient of Mn-doped 0.15Pb(In 1/2 Nb 1/2 )O 3 -0.57Pb(Mg 1/3 Nb 2/3 )O 3 -0.28PbTiO 3 (PIN-PMN-PT) single crystal is 0.0023 at 350 nm and decreases sharply to zero when the wavelength increases to larger than 450 nm. [22] X-ray diffraction (XRD) results in Figure S1a in the Supporting Information indicate that Sm-doped PMN-PT ceramics are all pure perovskite phase with pseudocubic structure, similar with La-doped PMN-PT transparent ceramics reported by Song et al [16] The single pseudocubic phase structure makes the birefringence scattering and secondary phases scattering negligible. Scattering loss caused by residual pores has been confirmed to be the main cause of the attenuation of the light intensity.…”
supporting
confidence: 63%
“…Details can be seen in previous articles. [16,17] Properties Characterization of PMN-PT Transparent Ceramics: The phase structure of Sm-0.88PMN-0.12PT transparent ceramics was characterized by XRD (Bruker D2 Phaser). Its microstructure was observed by SEM (JSM-6390LV).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ultrahigh piezoelectric coefficient (d 33 = 1500 pC/N) was obtained in Sm 3+ doped PMN-PT polycrystalline near MPB [1]. Because of the coupling function of excellent piezoelectric properties, efficient upconversion photoluminescence, and large electro-optic coefficient, RE (Pr 3+ , Yb 3+ , La 3+ , Er 3+ ) doped PMN-PT based ceramic were intensively investigated [7,[19][20][21][22].…”
Section: Introduction mentioning
confidence: 99%
“…During the photoluminescence process, low energy photons were absorbed while high energy photons were produced. For example, the La 3+ doped PMN-PT ceramics represented a high electro-optic (EO) coefficient on the value of 19.9×10 -16 (m/V) -2 [28,29], and a specific high optical transparency reaches up to 70% [19]. Therefore, the PMN-PT thin films doped with RE ions were expected to be multifunctional optical materials and deserved to be further investigated.…”
Section: Introduction mentioning
confidence: 99%